Investigation of Protective Effect of Matricaria Chamomilla L. Extract on Methotrexate-Induced Hepatotoxicity in Wistar Rat - Afarani,Maral Soltani (2020)
Abstract Methotrexate (MTX) was shown to cause oxidative stress and liver damage. The objective was to investigate the possible protective effects of Matricaria Chamomilla L. (chamomile) extract with anti-oxidant and anti-inflammatory properties on the methotrexate-induced liver toxicity. Twenty four Wistar rats were divided into four groups. MTX group was injected intraperitoneally on days 7 and 14 with 20 mg/kg methotrexate. Groups CE200 (chamomile extract 200 mg/kg/day) and CE300 (chamomile extract 300 mg/kg/day) received the same dose of methotrexate added with chamomile extract orally for 15 days at 200 mg/kg and 300 mg/kg respectively and the last group was healthy control group. Results of biochemical analyses indicated serum liver biomarkers (aminotransferases), alkaline phosphatase (ALP), albumin, and liver content of anti-oxidant enzymes (catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px)), reduced glutathione (GSH) and total anti-oxidant capacity (TAC) significantly increased (P <0.05-0.001) to normal in the CE treated groups compared to those of the MTX group. Serum bilirubin and hepatic malondialdehyde (MDA) levels significantly increased (P ˂0.001) in MTX group compared to those of the control group and decreased in CE200 and CE300 groups compared to those of the MTX group. Histopathological study showed inflammatory damage, necrotic cells and lipid infiltration in MTX group. In the groups treated with the chamomile extract, a significant improvement was observed in liver tissue in response to increased dose of the extract. In conclusion, chamomile extract administration could have a protective role in methotrexate-induced liver toxicity in rats through improving anti-oxidant defense system.